2019
DOI: 10.3390/math7050413
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Spherical Fuzzy Aggregation Operators and Their Applications in Multi-Attribute Decision Making Problems

Abstract: The key objective of the proposed work in this paper is to introduce a generalized form of linguistic picture fuzzy set, so-called linguistic spherical fuzzy set (LSFS), combining the notion of linguistic fuzzy set and spherical fuzzy set. In LSFS we deal with the vague and defective information in decision making. LSFS is characterized by linguistic positive, linguistic neutral and linguistic negative membership degree which satisfies the conditions that the square sum of its linguistic membership degrees is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 54 publications
1
48
0
1
Order By: Relevance
“…In Table 4, we derived the ranking order of the alternatives by utilizing the developed method. From Table 6, we observed that the ranking orders of the alternatives using the developed method were totally matched with those derived by the Jin et al [47] method. Therefore, the proposed technique is also validated.…”
Section: Comparative Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…In Table 4, we derived the ranking order of the alternatives by utilizing the developed method. From Table 6, we observed that the ranking orders of the alternatives using the developed method were totally matched with those derived by the Jin et al [47] method. Therefore, the proposed technique is also validated.…”
Section: Comparative Discussionsupporting
confidence: 53%
“…Therefore, the proposed technique is also validated. Utilizing the proposed technique, the best alternative is Q 1 , which is the same as the best alternative obtained by the Jin et al [47] method. Thus, the proposed technique is really prominent, because it can effectively avoid any loss of information which formerly occurred during linguistic information processing.…”
Section: Comparative Discussionmentioning
confidence: 99%
See 3 more Smart Citations